Design, fabrication and characterization of FeAl-based metallic-intermetallic laminate (MIL) composites. (15th August 2019) - Wang, Haoren; Harrington, Tyler; Zhu, Chaoyi; Vecchio, Kenneth S.
Abstract: FeAl-based MIL composites of various iron alloys were fabricated with an innovative "multiple-thin-foil" configuration and "two-stage reaction" strategy. Alternating stacked metal foils were reactive sintered via SPS at 600 °C and 1000 °C to grow intermetallics. The "multiple-thin-foil" configuration reduces reaction time, enables local chemical composition control and allows metal/intermetallic combinations, which cannot be produced via the conventional methods. Fe–FeAl, 430SS-FeAl, and 304SS-FeAl MIL composites can be synthesized with desired metallic/intermetallic ratios, where FeAl is the single intermetallic phase present in the composites. Microstructure analysis via SEM, EDS, and EBSD confirms phase identification and reveals the formation of transition layers. The transition layer, which incorporates the composition gradient between the metal (Fe, 430SS or 304SS) and the FeAl intermetallic phase, provides a gradual change in mechanical properties from the metal to intermetallic layers, and further functions as a chemical barrier into which other undesired intermetallics dissolve. Driven by diffusion-controlled growth, grains in the transition layers and FeAl regions exhibit ordered arrangement and sintering textures. Hardness profiles from the metal layer to FeAl region reveal the correlation between local mechanical properties and local chemical compositions. In compression testing, the compressive strength can reach 2.3 GPa with considerable plasticity, establishing the best mechanical properties of any MIL composites synthesized to date. Graphical abstract: Image 1